Description of Alphasat Satellite Space Motion and Its Consequences for Signal Reception - Pek, Viktor; Brázda, Vladimír; Fišer, Ondřej (IEEE (Institute of Electrical and Electronics Engineers), 2016)
The article deals with description of spatial motion of the experimental radio-communications satellite Alphasat. The used Cartesian coordinates of the Alphasat satellite (given one week in advance in the OEM files of 5 minute resolution) are described. The coordinates conversion to the elevation and azimuth from the perspective of the receiver in Prague is added and described. This satellite motion causes some problems with signal reception - automatic antenna tracking is required or at least the antenna beam width extension. We found that the elevation of the Alphasat currently fluctuates up to 2,5 ° ; in the case of azimuth it is up to 0.5° in Prague. The time period of these changes is 23 hours and 56 minutes. And more, also long-term trends of elevation/azimuth are described in this contribution.
Popis pohybu satelitu Alphasat a jeho důsledky pro příjem signálu
Keywords: Satellite propagation, satellite motion, Alphasat, elevation, azimuth; Družicové šíření, družicový pohyb, Alphasat, elevace, azimut